2018
DOI: 10.1093/toxsci/kfy228
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Mice With Humanized Livers Demonstrate Human-Specific Hepatotoxicity Caused by a Therapeutic Antibody Against TRAIL-Receptor 2/Death Receptor 5

Abstract: The activation of tumor necrosis factor (TNF)-related apoptosis-inducing ligand receptor 2 (TRAIL-R2)/death receptor 5 (DR5) induces apoptosis in various tumor cells but not in normal human cells. Since some therapeutic antibodies targeting TRAIL-R2 have demonstrated severe hepatotoxicity in clinical applications, novel in vivo models reflecting clinical hepatotoxicity are now required. In this study, we investigated the hepatotoxicity caused by KMTR2, an anti-human TRAIL-R2 monoclonal antibody, in chimeric mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…These results indicate that PXB mice can be useful tools for the evaluation of porphyrogenic in vivo human hepatotoxicity, which complements other studies of hepatotoxicants. 14 18 Also, yellowish-brown pigment was observed in association with the hepatocellular injury which stained with Berlin blue and Schmorl stains ( Table 1 and Figure 3 ), indicating the presence of iron and lipofuscin deposition, respectively. Iron accumulation is considered secondary to porphyria-related perturbation of heme biosynthesis based on evidence that porphyrogenic compounds induce iron deposition in the liver.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results indicate that PXB mice can be useful tools for the evaluation of porphyrogenic in vivo human hepatotoxicity, which complements other studies of hepatotoxicants. 14 18 Also, yellowish-brown pigment was observed in association with the hepatocellular injury which stained with Berlin blue and Schmorl stains ( Table 1 and Figure 3 ), indicating the presence of iron and lipofuscin deposition, respectively. Iron accumulation is considered secondary to porphyria-related perturbation of heme biosynthesis based on evidence that porphyrogenic compounds induce iron deposition in the liver.…”
Section: Discussionmentioning
confidence: 98%
“… 11 13 Chimeric mouse livers consist of human hepatocytes with a small percentage of mouse hepatocytes and mouse hepatic sinusoidal cells (mainly Kupffer cells, endothelial cells, and stellate cells), and the human hepatocytes have been shown to cooperate with mouse hepatic sinusoidal cells in carrying out liver functions. 12 Given these characteristics, PXB mice have been widely used for evaluation of hepatotoxicity induced by chemical compounds 14 17 or therapeutic antibodies, 18 and also for MOA studies for hepatocellular carcinogenesis. 19 21 However, the key events of the porphyria-mediated cytotoxicity MOA have not yet been evaluated using PXB mice, and thus the present study was conducted to assess whether these key events could be detected in PXB mice by using a representative porphyrinogenic compound.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study using the same chimeric human hepatocyte mouse model (PXB-mouse, cDNA-uPA/SCID), treatment with KMTR2 (an anti-human tumor necrosis factor (TNF)-related apoptosis-inducing ligand receptor 2 (TRAIL-R2) monoclonal antibody) was shown to induce hepatotoxicity and apoptosis in human hepatocytes, which is associated with an upregulation of cell cycle-related functions likely representing cellular regeneration 89 . Ishida et al.…”
Section: Car-dependent Hepatocyte Proliferationmentioning
confidence: 99%
“…cDNA-uPA/SCID), treatment with KMTR2 (an anti-human tumor necrosis factor (TNF)-related apoptosis-inducing ligand receptor 2 (TRAIL-R2) monoclonal antibody) was shown to induce hepatotoxicity and apoptosis in human hepatocytes, which is associated with an upregulation of cell cycle-related functions likely representing cellular regeneration89 . Ishida et al reported that the cytotoxicity of aflatoxin B1 was detected by using histological examination and biochemical analysis in chimeric mice with human hepatocytes (PXB-mouse, cDNA-uPA/SCID), although hepatocyte proliferation was not examined90 .…”
mentioning
confidence: 99%
“…Despite that fact that TRAIL-based therapies were generally well tolerated, phase I/II clinical trials for a wide variety of cancers resulted in poor responses for the vast majority of patients [211][212][213][214][215][216]. Withal, different resistance mechanisms seem to limit the success of TRAIL-based therapies: (i) low persistence of recombinant TRAIL, (ii) whereas agonistics antibodies are receptor specific, recombinant TRAIL also binds to decoy receptors, (iii) depending on the tumor, TRAIL receptor apoptotic signaling preferably relies on TRAIL-R1 or TRAIL-R2, so agonistic mAbs to specific receptors must be carefully chosen [217][218][219][220], (iv) agonistic mAbs are weak apoptosis-inducers due the lack of death receptor homotrimers (reviewed in [21] and [221]) and, (v) in some cases, severe hepatotoxicity was detected [222][223][224][225]. Due to the lack of success of recombinant TRAIL and agonistic mAbs as monotherapy, combinatorial therapies along with CDK9 inhibitors or SMAC mimetics among others have currently been studied [226][227][228][229][230].…”
Section: Resistance To Death Receptors-mediated Cell Deathmentioning
confidence: 99%